Cell-free osteoarthritis treatment with dual-engineered chondrocyte-targeted extracellular vesicles derived from mechanical loading primed mesenchymal stem cells - Peng Wang; Haiyue Zhao; Wei Chen; Yuhui Guo; Shuo Zhang; Xin Xing; Shuai Yang; Fengkun Wang; Juan Wang; Zengwu Shao; Yingze Zhang (Journal of Tissue Engineering)
Osteoarthritis (OA) is an age-related chronic inflammatory disease, predominantly characterized by chondrocyte senescence and extracellular matrix (ECM) degradation. Although mesenchymal stem cells (MSCs) derived extracellular vesicles (EVs) are promising for promoting cartilage regeneration, their clinical application is limited by inconsistent therapeutic effects and insufficient targeting capabilities. Mechanical loading shows potential to optimize MSC-EVs for OA treatment, while the underlying mechanism is not clear. In this study, EVs derived from mechanical loading-primed MSCs (ML-EVs) demonstrate prominent efficacy in maintaining ECM homeostasis and relieving chondrocyte senescence, thereby mitigating OA. Subsequent miRNA sequencing reveals that ML-EVs exert their effects by delivering miR-27b-3p, which targets ROR1 mRNA in chondrocytes and suppresses downstream NF-κB pathways. By modulating the ROR1/NF-κB axis, miR-27b-3p effectively restrains ECM degradation and chondrocyte senescence. To optimize therapeutic efficacy of EVs, miR-27b-3p is overexpressed within EVs (miR OE -EVs), and a chondrocyte-targeted peptide (CTP) is conjugated to their surface, thereby constructing dual-engineered chondrocyte-targeted EVs (CTP/miR OE -EVs). CTP/miR OE -EVs exhibit excellent ability to specifically target cartilage and ameliorate OA pathology. In conclusion, this study underscores the critical role of mechanical loading in augmenting effectiveness of EVs in mitigating OA and introduces dual-engineered EVs that specifically target chondrocytes, providing a promising therapeutic strategy for OA.